ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN UMKM MENGGUNAKAN QRIS DAN PENGARUHNYA TERHADAP PENGHASILAN UMKM DI PASAR RAKYAT KOTA MALANG - Micke Theresa Bella Alfira; Susilo (Contemporary Studies in Economic, Finance and Banking, 2023)
The massive payment using electronic money which can now be used in almost all transactions including shopping centers, thus encouraging Bank Indonesia to establish QRIS (Quick Response Code Indonesian Standard) as the payment QR code standard, where to expand the implementation of QRIS, Bank Indonesia issued the SIAP Markets and Shopping Center program (Healthy, Innovative, Safe to Use) QRIS. This study discusses the influence of technological, organizational, and environmental factors on the decision of MSMEs to use QRIS and their impact on MSME income in the Malang City market. 96 samples were used with a sample size following the Cochran formula and purposive sampling technique and the PLS-SEM method as the analysis with SmartPLS. The findings indicate that technology, organization and the environment have a positive and significant influence on MSME’s decisions to use QRIS and the use of QRIS has a positive and significant influence on MSME income.